y = 3Cosx + 2Sin²x - 1
Найдём производную :
y' = (Cosx)' + 2(Sin²x)' - 1' = - 3Sinx + 4SinxCosx
Приравняем производную к нулю :
- 3Sinx + 4SinxCosx = 0
Sinx(- 3 + 4Cosx) = 0
Sinx = 0
- 3 + 4Cosx = 0
Cosx = 0,75
Если Sinx = 0 , то Cosx = ± 1
1) Sinx = 0 ⇒ Cosx = - 1 ⇒
y = 3 * (- 1) + 2 * 0 - 1 = - 4 - наименьшее
2) Sinx = 0 ⇒ Cosx = 1 ⇒
y = 3 * 1 + 2 * 0 - 1 = 2
3) Cosx = 0,75 ⇒ Sin²x = 1 - Cos²x = 1 - 0,75² = 1 - 0,5625 = 0,4375
y = 3 * 0,75 + 2 * 0,4375 - 1 = 2,25 + 0,875 - 1 = 2,125 - наибольшее
ответ : наименьшее - 4 , наибольшее 2,125
x²+6x+5=0
x1+x2=-6 U x1*x2=5⇒x1=-5 U x2=-1
f(x)=3/5ln[(x+1)(x+5)]=3/5ln(x+1)+3/5ln(x+5)
1)f1(x)=ln(x+1)=x-x²/2+x³/3-x^4/4+...+(-1)^n*x^n/n
2)f2(x)=ln(x+5)=ln[5(1+x/5)]=ln5+ln(1+x/5)=
=ln5+x/5-x²/2*5²+x³/3*5^3-x^4/4*5^4+...+(-1)^n*x^n/n*5^n
f(x)=3/5*[x-x²/2+x³/3-x^4/4+...+(-1)^n*x^n/n +ln5+x/5-x²/2*5²+x³/3*5^3-x^4/4*5^4+...+(-1)^n*x^n/n*5^n)=3/5*(ln5+6x/5-26x²/50+126x^3/375-
-626x^4/22500+...+(-1)^n*[(5^n*+1)*x^n)]/(n*5^n)]